Spot diagnosis of intermittent gastrointestinal bleeding - Baars, Judith E.; Aslam, Perveen; Kaffes, Arthur J.; Saxena, Payal (Endoscopy International Open, 2018)
Background and study aims In this case report with video, we present a unique image of a rare, but important cause of gastrointestinal bleeding which often is missed due to its intermittent nature.